The influence of the sprayer control on the increase in the productivity of the machine-tractor aggregate in the protection of orchards - Maličević Zoran; Jugović Milan; Mitrić Siniša; Mitrović Dragoljub (Agroznanje, 2019)
For the chemical protection of orchards, a research on the surface area of 150 ha was carried out, and a method of spraying was applied. In this method, machines known as orchard sprayer are used, in which, in the presence of the produced air current, liquid disintegration is also carried out at a drop size of 50 to 150 mm. The aim of the research is to improve the precision of work within the control of the device, where the emphasis on the nozzle capacity is primarily augmented, and therefore increases the productivity of the device. The results obtained on the basis of a 10-hour working time prove that the exploitation of the controlled orchard sprayer ensures greater productivity by 2.24 ha on a plot distanced 50 m from the location of the tank refill, i.e., 2.20 ha on a plot distanced 2000 m from the location of the tank refill, for the drawn sprayer of 1.000 l volume. By analyzing the total energy inputs of orchard protection, different application models point to a smaller energy input when using controlled devices on a 50 m range for 7.58%. Energy inputs on a longer distance plot are by 24.68% lower in favor of the treatment of controlled sprayer.